2009
DOI: 10.1186/1471-2458-9-281
|View full text |Cite
|
Sign up to set email alerts
|

HIV sexual risk behaviors and perception of risk among college students: implications for planning interventions

Abstract: BackgroundThe college environment offers great opportunity for HIV high-risk behaviors, including unsafe sex and multiple partnerships. While the overall incidence of HIV infection has seen some decline in recent years, rates of HIV infection among young adults have not seen a proportionate decline. As in the general population, African American young adults have been disproportionately affected by the HIV/AIDS epidemic. This study examined the sexual risk behaviors and perception of HIV risk of students in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
100
3
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(125 citation statements)
references
References 27 publications
(30 reference statements)
8
100
3
6
Order By: Relevance
“…The acute effects of alcohol can also increase risk-taking behavior by narrowing an individual's focus to only the most salient cues in the environment, a process referred to as alcohol myopia (Steele and Josephs, 1990;Taylor and Leonard, 1983). In a sexual encounter involving alcohol, the most salient cue may be sexual arousal rather than the potential risk associated with a sexual partner (e.g., Davis et al, 2007;George et al, 2009;MacDonald et al, 2000), thereby increasing the likelihood of risk-taking behavior (Adefuye et al, 2009).…”
mentioning
confidence: 99%
“…The acute effects of alcohol can also increase risk-taking behavior by narrowing an individual's focus to only the most salient cues in the environment, a process referred to as alcohol myopia (Steele and Josephs, 1990;Taylor and Leonard, 1983). In a sexual encounter involving alcohol, the most salient cue may be sexual arousal rather than the potential risk associated with a sexual partner (e.g., Davis et al, 2007;George et al, 2009;MacDonald et al, 2000), thereby increasing the likelihood of risk-taking behavior (Adefuye et al, 2009).…”
mentioning
confidence: 99%
“…In a sample of 390 students, having consumed at least one drink in the past 30 days was associated with not using a condom in both males (OR 1.24, CI 0.57-2.72, p≤0.05) and females (OR 1.81, CI 1.06-3.10, p=0.04). Having consumed alcohol in the past 30 days was a predictor of no condom use for females, especially those over 30 years of age (OR 3.43, CI 1.33-8.86, p=0.01) (Adefuye et al, 2009). The implications of this finding must be considered in light of the fact that many of these women also report fewer partners, and condom use is overall low in monogamous relationships (Adefuye et al, 2009).…”
Section: United Statesmentioning
confidence: 94%
“…Having consumed alcohol in the past 30 days was a predictor of no condom use for females, especially those over 30 years of age (OR 3.43, CI 1.33-8.86, p=0.01) (Adefuye et al, 2009). The implications of this finding must be considered in light of the fact that many of these women also report fewer partners, and condom use is overall low in monogamous relationships (Adefuye et al, 2009). No link between number of sexual partners and condom use was found (Sheer and Cline, 1995;Randolph et al, 2009).…”
Section: United Statesmentioning
confidence: 94%
See 1 more Smart Citation
“…[5] Several reviews of the general population indicate a possible relationship between poor mental health, including substance use, and HIV risk behaviour, such as multiple sexual partners and unprotected sex. [6][7][8][9][10][11][12][13] Studies conducted among university students found that anxiety, [14] depression, [14,15] psychological distress, [15] alcohol use, [15][16][17][18][19][20] drug use, [19,20] and traumatic experiences [21] (in particular childhood abuse, physical abuse, and especially sexual abuse [22] ) were associated with various forms of HIV risk behaviour. Currently, there are not sufficient data on university students regarding the association between mental disorders, substance use and HIV sexual risk behaviour within the SA context.…”
mentioning
confidence: 99%